Pengajaran Mata Kuliah Korespondensi Bisnis Jepang di Jurusan Sastra Jepang - Binus University Jakarta - Elisa Carolina Marion (Humaniora, 2011)
One of the purposes of studying a foreign language one is to support the ability / skills later used in the workforce. One of the skills / abilities needed by learners is the ability in business correspondence. Binus University offers a compulsory specialization course for students in their sixth semester namely translation and office. Japanese business correspondence courses is one of the compulsory subjects contained in the specialization in office for the sixth semester students. Problems contained in Binus University are that most students who took office specialization dislike grammar, kanji, and others. This problem is quite significant in the process of teaching and learning so that teachers should use other media such as discussion forums on Binusmaya to maximize the teaching and learning in the classroom and also help students who lack the ability to make sentences with the correct and appropriate sentence pattern.